Hubungan Tingkat Pengetahuan dan Dukungan Keluarga dengan Keinginan Berhenti Merokok Siswa - Puput Rahmawati; Nutrisia Nu’im Haiya; Iwan Ardian; Intan Rizmatul Azizah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Smokers in Indonesia are increasing every year, cigarettes are one of the bad effects on health that are not only detrimental to smokers but also have a bad impact on the people around them, some of the factors that can influence a person to quit smoking are the level of knowledge of the dangers of cigarettes and good family support. The purpose of this study is to determine the relationship between the level of knowledge and family support and the desire to quit smoking in students Quantitative research, independent variables of knowledge and family support, dependent variables of desire to quit smoking, using a cross-sectional study design, descriptive analytical approach, with a total sampling technique of 90 respondents using a valid and reliable questionnaire. The analysis uses the Somers'd test The level of knowledge showed a good category of 73.4%, medium family support of 75.6% while the desire to quit smoking was a high category of 49.2%. The relationship between the level of smoking knowledge and the desire to quit smoking of students was significant with a p value of 0.000, a correlation value of 0.602, a strong category correlation, a positive relationship direction while the relationship between family support and a significant desire to quit smoking was a p value of 0.000, a correlation value of 0.424, a moderate category correlation, a positive relationship Conclusion: There is a relationship between the level of knowledge and family support and the desire to quit smoking of students. The research has a positive impact on encouraging students' awareness to stay away from smoking habits so that they can implement a good lifestyle in the community. The researchers suggested that a larger number of samples could be involved with more than 1 observation and use other study designs in the study.